Regularity of Tensor Products Of k-Algebras - Bouchiba, S.; Kabbaj, S. (MATHEMATICA SCANDINAVICA, 2014)
This paper tackles a problem on the possible transfer of regularity to tensor products of algebras over a field k. The main result establishes necessary and sufficient conditions for a Noetherian tensor product of two extension fields of k to inherit regularity in various settings of separability. Thereby, we provide some applications as well as several original examples to illustrate or delimit the scope of the established results.